POLICY ENTREPRENEURSHIP AND POPULATION ADMINISTRATION INNOVATION IN GREDEK VILLAGE - Muhammad Bahrul Ghofar; Ika Devy Pramudiana; Dian Ferriswara (International Journal of Multidisciplinary Reseach, 2026)
Population administration services at the village level often experience innovation stagnation due to weak leadership initiative, limited institutional capacity, and bureaucratic resistance. This study analyzes policy entrepreneurship by the Village Head of Gredek, Gresik Regency, in promoting innovation in population administration services and identifies the supporting and inhibiting factors shaping the process. A qualitative instrumental case study was employed. Data were collected through in-depth interviews with seven purposively selected informants, non-participant observation, and document review. Data analysis followed the interactive model of Miles, Huberman, and Saldana through data condensation, data display, and conclusion drawing and verification. The findings show that the village head performed a comprehensive policy entrepreneurship role through social acuity, layered problem framing, mutually beneficial coalition building, proactive use of policy windows, and evidence-based piloting. These practices produced six service innovations, reduced average document processing time by approximately 79%, and increased citizen satisfaction from 2.8 to 4.3 on a five-point scale. The study strengthens policy entrepreneurship literature in Indonesian village governance.